Simulated kinetic effects of the corona and solar cycle on high altitude ion transport at Mars. Issue 6 (17th June 2013) - Curry, S. M.; Liemohn, M.; Fang, X.; Brain, D.; Ma, Y.
Abstract : [1] We present results from the Mars Test Particle (MTP) simulation as part of a community‒wide model comparison in order to quantify the role of different neutral atmospheric conditions in planetary ion transport and escape. This study examines the effects of individual ion motion by simulating particle trajectories for three cases: solar minimum without the neutral corona, solar minimum with the inclusion of the neutral corona, and solar maximum with the inclusion of the neutral corona. The MTP simulates 1.5 billion test particles through background electric and magnetic fields computed by a global magnetohydrodynamic model. By implementing virtual detectors in the simulation, the MTP has generated velocity space distributions of pickup ions and quantifies the ion acceleration at different spatial locations. The study found that the inclusion of a hot neutral corona greatly affects the total O + production and subsequent loss, roughly doubling the total escape for solar minimum conditions and directly contributing to high energy sources above 10 keV. The solar cycle influences the amount of O + flux observed by the virtual detectors, increasing the O + flux and total escape by an order of magnitude from solar minimum to maximum. Additionally, solar maximum case induces greater mass loading of the magnetic fields, which decreases the gyroradius of the ions and redirects a significant ion population downtail to subsequently escape. Key Points: Corona doubles O+ escape at solar min and contributes to ions accelerated >10keV Solar cycle increases O+ flux and escape by order of magnitude Solar max case induces smaller O+ gyroradius redirects ions downtail to escape